Pengaruh Waktu Pemangkasan Wiwilan dan Pemberian Pupuk NPK terhadap Produksi Tanaman Tomat (Lycopersicum Esculentum Mill) - Mawar Mawar; Akriandi Amin; Nurkamila Sari (Journal of Creative Student Research, 2026)
This study aimed to (1) determine the effect of wiwilan pruning timing on the growth and production of tomato plants. (2) determine the effect of NPK fertilizer application on the growth and production of tomato plants. (3) determine the interaction between wiwilan pruning timing and NPK fertilizer application on the growth and production of tomato plants. This study was conducted in Gareccing Hamlet, Talle Village, South Sinjai District, Sinjai Regency. The study ran from May to August 2025. The used experimental design was a randomized block design with two factors arranged in a Randomized Block Design (RBD). The first factor was pruning (P), which consisted of four treatment levels: P0: No pruning (Control), P1: 25 days after planting, P2: 35 days after planting, and P3: 45 days after planting. The second factor was the application of Mutiara 16:16:16 NPK fertilizer (N), which consisted of four treatment levels: N0 = without Mutiara NPK fertilizer (Control), N1 = 3 g Mutiara NPK fertilizer/polybag, N2 = 4 g Mutiara NPK fertilizer/polybag, N3 = 5 g Mutiara NPK fertilizer/polybag. The results showed that pruning at 45 days after planting significantly affected the number of fruits (14.58 fruits) and weight (103.5 grams). The 5 g NPK fertilizer/plant treatment significantly affected plant height (56.3 cm) and number of fruits (12.5 fruits). The interaction treatment between pruning at 35 days after planting (P2) and 4 g Mutiara NPK fertilizer/polybag (N2) resulted in the highest average number of branches, at 16.2.